2015
DOI: 10.12688/f1000research.7010.1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IL-10 and IL-12 production and function in macrophages and dendritic cells

Abstract: Interleukin-10 and Interleukin-12 are produced primarily by pathogen-activated antigen-presenting cells, particularly macrophages and dendritic cells. IL-10 and IL-12 play very important immunoregulatory roles in host defense and immune homeostasis. Being anti- and pro-inflammatory in nature, respectively, their functions are antagonistically opposing. A comprehensive and in-depth understanding of their immunological properties and signaling mechanisms will help develop better clinical intervention strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
175
2
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(197 citation statements)
references
References 149 publications
11
175
2
9
Order By: Relevance
“…The study also reported that along with the elevation of IFN- In specific cellular immunity, IL-12 is notably associated with the stimulation of IFN-γ production by NK and T cells as well as the augmentation of NK cell cytotoxicity [77].…”
Section: Vaginal Candidiasismentioning
confidence: 75%
“…The study also reported that along with the elevation of IFN- In specific cellular immunity, IL-12 is notably associated with the stimulation of IFN-γ production by NK and T cells as well as the augmentation of NK cell cytotoxicity [77].…”
Section: Vaginal Candidiasismentioning
confidence: 75%
“…+ T cells to become interferon--producing T helper 1 (Th1) effectors in cell-mediated immune responses [28]. IL-12 could also synergize with B7/CD28 interaction in inducing efficient proliferation and cytokine production of human T cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 is a pleiotropic pro-inflammatory cytokine that activates the immune system via multiple mechanisms and is expressed by several immune cells including dendritic cells, macrophages and neutrophils [19]. IL-12 is a key Th1-polarizing cytokine along with IFN-γ [20].…”
Section: Il-12 As a Cancer Therapeuticmentioning
confidence: 99%